2024
DOI: 10.1038/s41598-023-50634-y
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of circulating monocytes in maintaining homeostasis of resident macrophages in postnatal and young adult mouse cochlea

Toru Miwa,
Gowshika Rengasamy,
Zhaoyuan Liu
et al.

Abstract: The percentage of macrophage subpopulations based on their origins in the adult cochlea remains unclear. This study aimed to elucidate the origins of cochlear macrophages during the onset phase and development of auditory function. We used three types of mice: wildtype ICR mice, colony-stimulating factor 1 receptor (Csf1r)-deficient mice, and Ms4a3Cre-Rosa tdTomato (Ms4a3tdT) transgenic mice. Macrophages were labeled with ionized calcium-binding adapter molecule 1 (Iba1), which is specific to more mature macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Experiments have shown that innate immune cells enter the perilymph through the spiral ligament ( 67 ) whereas lymphocytes enter through modiolar venules ( 68 ). Moreover, lateral wall macrophages (and a subpopulation of spiral ligament fibrocytes) derive from bone marrow cells ( 69–71 ) and the proportion of bone marrow-derived macrophages increases with age ( 72 ). Our data would support a local bone marrow production of innate cells reaching the lateral wall, as in the brain ( 48 ), since both CAEM and VEM are connected to the spiral ligament and external cochlear wall but not to the cochlear modiolus.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that innate immune cells enter the perilymph through the spiral ligament ( 67 ) whereas lymphocytes enter through modiolar venules ( 68 ). Moreover, lateral wall macrophages (and a subpopulation of spiral ligament fibrocytes) derive from bone marrow cells ( 69–71 ) and the proportion of bone marrow-derived macrophages increases with age ( 72 ). Our data would support a local bone marrow production of innate cells reaching the lateral wall, as in the brain ( 48 ), since both CAEM and VEM are connected to the spiral ligament and external cochlear wall but not to the cochlear modiolus.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages in the Inner Ear: Discoveries and Innovative Techniques Illustrating Their Key… DOI: http://dx.doi.org/10.5772/intechopen.1005106 Some studies have shown that inner ear macrophages can also arise from resident precursor cells in the inner ear [7,17].…”
Section: Complex Origin Of Inner Ear Macrophages From Embryonic Devel...mentioning
confidence: 99%
“…population that is regularly renewed by monocytes in the bloodstream [7,18]. In the stria vascularis of the mature cochlea, resident macrophages can be distinguished by the expression of markers, such as F4/80, CD68, Iba1, and CD11b [18][19][20], and they are primarily positioned close to blood vessels, serving as perivascular macrophages (PVMs).…”
Section: Red) (A) a Mid-modiolar Paraffin-section Of The Adult Cochle...mentioning
confidence: 99%
See 1 more Smart Citation